Laboratory and field measurements of enantiomeric monoterpene emissions as a function of chemotype, light and temperature - Song, W; Staudt, M; Bourgeois, I; Williams, J (BIOGEOSCIENCES, 2014)
Plants emit significant amounts of monoterpenes into the earth's atmosphere, where they react rapidly to form a multitude of gas phase species and particles. Many monoterpenes exist in mirror-image forms or enantiomers. In this study the enantiomeric monoterpene profile for several representative plants (Quercus ilex L., Rosmarinus officinalis L., and Pinus halepensis Mill.) was investigated as a function of chemotype, light and temperature both in the laboratory and in the field. Analysis of enantiomeric monoterpenes from 19 Quercus ilex individuals from Southern France and Spain revealed four regiospecific chemotypes (genetically fixed emission patterns). In agreement with previous work, only Quercus ilex emissions increased strongly with light. However, for all three plant species no consistent enantiomeric variation was observed as a function of light, and the enantiomeric ratio of alpha-pinene was found to vary by less than 20% from 100 and 1000 mu mol m(-2) s(-1) PAR (photosynthetically active radiation). The rate of monoterpene emission increased with temperature from all three plant species, but little variation in the enantiomeric distribution of alpha-pinene was observed with temperature. There was more enantiomeric variability between individuals of the same species than could be induced by either light or temperature. Field measurements of alpha-pinene enantiomer mixing ratios in the air, taken at a Quercus ilex forest in Southern France, and several other previously reported field enantiomeric ratio diel cycle profiles are compared. All show smoothly varying diel cycles (some positive and some negative) even over changing wind directions. This is surprising in comparison with variations of enantiomeric emission patterns shown by individuals of the same species.
APS
Keywords: Monoterpenes; Pinus halepensis Mill.; Quercus ilex L.; Rosmarinus officinalis L.

Drought reduced monoterpene emissions from the evergreen Mediterranean oak Quercus ilex: results from a throughfall displacement experiment - a.-V. Lavoir; Staudt, M; Schnitzler, J P; Landais, D; Massol, F; Rocheteau, A; Rodriguez, R; Zimmer, I; Rambal, S (Biogeosciences, 2009)
The effects of water limitations on the emission of biogenic volatile organic compounds are not well understood. Experimental approaches studying drought effects in natural conditions are still missing. To address this question, a throughfall displacement experiment was set up in a natural forest of Quercus ilex, an evergreen Mediterranean oak emitting monoterpenes. Mature trees were exposed in 2005 and 2006 either to an additional drought, to irrigation or to natural drought (untreated control). In both years, absolute monoterpene emission rates as well as the respective standard factors of the trees exposed to normal and additional drought strongly declined during the drought periods. Monoterpene emissions were lower in year 2006 than in year 2005 (factor 2) due to a more pronounced summer drought period in this respective year. We observed a signiﬁcant difference between the irrigation and additional drought or control treatment: irrigated trees emitted 82% more monoterpenes during the drought period 2006 than the trees of the other treatments. However, no signiﬁcant effect on monoterpene emission was observed between normal and additional drought treatments, despite a signiﬁcant effect on leaf water potential and photochemical efﬁciency. During the development of drought, monoterpene emissions responded exponentially rather than linearly to decreasing leaf water potential. Emissions rapidly declined when the water potential dropped below −2 MPa and photosynthesis was persistently inhibited. Monoterpene synthase activities measured in vitro showed no clear reduction during the same period. From our results we conclude that drought signiﬁcantly reduces monoterpene ﬂuxes of Mediterranean Holm oak forest into the atmosphere due to a lack of primary substrates coming from photosynthetic processes
Keywords: BVOC emission; Drought; Quercus ilex (voyant); Water availability

Process-based modelling of isoprenoid emissions from evergreen leaves of Quercus ilex (L.) - Grote, R; Mayrhofer, S; Fischbach, R J; Steinbrecher, R; Staudt, M; Schnitzler, J.-P. (Atmospheric Environment, 2006)
Monoterpenes play an important role in regulating the trace gas composition of the lower troposphere. Therefore, realistic estimates of the daily as well as seasonal variations of monoterpene emission source strength on the Earth surface are required. Monoterpenes are emitted by Holm oak (Quercus ilex L.) and other species lacking speciﬁc foliar terpene storage structures and their development is dependent on light and temperature. In the present work we describe a process-based emission model taking into account the physiological/phenological state of Holm oak leaves and biochemical processes leading to the formation of monoterpenes. The model ‘seasonal isoprenoid synthase model–biochemical isoprenoid biosynthesis model’ (SIM–BIM2) is developed based on a previous version which was used to simulate isoprene emissions from deciduous oaks. The current model considers additional enzymatic reactions in Holm oak chloroplasts that lead to the formation of monoterpenes. The comparison of simulated and measured biochemical properties as well as emission rates displayed that the ability of the model to dynamically adjust monoterpene biosynthesis capacity by modulating the amount of monoterpene synthase activities in dependence of the weather pattern led to realistic simulations of light-dependent monoterpene emission rates. Differences to simulation results obtained by a widely used alternative model [Guenther, A.B., Zimmerman, P.R., Harley, P.C., Monson, R.K., Fall, R., 1993. Isoprene and monoterpene emission rate variability—model evaluations and sensitivity analyses. Journal of Geophysical Research 98, 12609–12617] are discussed.
Keywords: model development; monoterpene emission rates; monoterpene synthases; Quercus ilex; Seasonality; sim-bim2

Biogenic volatile organic compounds (VOC): An overview on emission, physiology and ecology - Kesselmeier, J; Staudt, M (JOURNAL OF ATMOSPHERIC CHEMISTRY, 1999)
This overview compiles the actual knowledge of the biogenic emissions of some volatile organic compounds (VOCs), i.e., isoprene, terpenes, alkanes, alkenes, alcohols, esters, carbonyls, and acids. We discuss VOC biosynthesis, emission inventories, relations between emission and plant physiology as well as temperature and radiation, and ecophysiological functions. For isoprene and monoterpenes, an extended summary of standard emission factors, with data related to the plant genus and species, is included. The data compilation shows that we have quite a substantial knowledge of the emission of isoprene and monoterpenes, including emission rates, emission regulation, and biosynthesis. The situation is worse in the case of numerous other compounds (other VOCs or OVOCs) being emitted by the biosphere. This is reflected in the insufficient knowledge of emission rates and biological functions. Except for the terpenoids, only a limited number of studies of OVOCs are available; data are summarized for alkanes, alkenes, carbonyls, alcohols, acids, and esters. In addition to closing these gaps of knowledge, one of the major objectives for future VOC research is improving our knowledge of the fate of organic carbon in the atmosphere, ending up in oxidation products and/or as aerosol particles.
Keywords: acids; alkanes; alkenes; carbonyls; ecology; emission; emission inventories; Esters; isoprene; nonmethane hydrocarbons; oxygenated compounds; physiology; review; terpenes; Volatile Organic Compounds

Light and temperature dependence of the emission of cyclic and acyclic monoterpenes from holm oak (Quercus ilex L.) leaves - Staudt, M; Bertin, N (Plant, Cell & Environment, 1998)
In a laboratory study, we investigated the monoterpene emissions from Quercus ilex, an evergreen sclerophyllous Mediterranean oak species whose emissions are light dependent. We examined the light and temperature responses of individual monoterpenes emitted from leaves under various conditions, the effect of heat stress on emissions, and the emission-onset during leaf development. Emission rate increased 10-fold during leaf growth, with slight changes in the composition. At 30 °C and saturating light, the monoterpene emission rate from mature leaves averaged 4·1 nmol m–2 s–1, of which α-pinene, sabinene and β-pinene accounted for 85%. The light dependence of emission was similar for all monoterpenes: it resembled the light saturation curve of CO2 assimilation, although monoterpene emission continued in the dark. Temperature dependence differed among emitted compounds: most of them exhibited an exponential increase up to 35 °C, a maximum at 42 °C, and a slight decline at higher temperatures. However, the two acyclic isomers cis-β-ocimene and trans-β-ocimene were hardly detected below 35 °C, but their emission rates increased above this temperature as the emission rates of other compounds fell, so that total emission of monoterpenes exponentially increased from 5 to 45 °C. The ratio between ocimene isomers and other compounds increased with both absolute temperature and time of heat exposure. The light dependence of emission was insensitive to the temperature at which it was measured, and vice versa the temperature dependence was insensitive to the light regime. The results demonstrated that none of the models currently applied to simulate isoprene or monoterpene emissions correctly predicts the short-term effects of light and temperature on Q. ilex emissions. The percentage of fixed carbon lost immediately as monoterpenes ranged between 0·1 and 6·0% depending on temperature, but rose up to 20% when leaves were continuously exposed to temperatures between 40 and 45 °C.
Keywords: biogenic VOC emission; emission model; heat stress; Holm oak; Isoprenoids; light effect; Monoterpenes; Quercus ilex; temperature effect

Diurnal and seasonal course of monoterpene emissions from Quercus ilex(L.) under natural conditions application of light and temperature algorithms - Bertin, N; Staudt, M; Hansen, U; Seufert, G; Foster, P; Fugit, J L; Torres, L (Atmospheric Environment, 1997)
Quercus ilex is a common oak species in the Mediterranean vegetation and a strong emitter of monoterpenes. Since the short-term control of monoterpene emissions from this species involved both temperature and light, the usual exponential function of temperature may not be sufficient to model the diurnal and seasonal emission course. In the frame of the BEMA-project (Biogenic Emissions in the Mediterranean Area), we investigated the tree-to-tree, branch-to-branch, diurnal, and seasonal variability of monoterpene emissions from Q. ibex over one and a half years at Castelporziano (Rome, Italy). In addition, w,: checked the suitability of the model developed for isoprene by Guenther et al. (1991, 1993) to simulate the short- and long-term variations of monoterpene emissions from this particular species. We found that the tree-to-tree variability was rather small compared to the experimental error during air sampling and analysis by diverse laboratories. The branch-to-branch variability was noticeable between sun- and shade-adapted branches only. 80% of total emissions were represented by cc-pinene, B-pinene and sabinene, whose proportions were stable over the year and independent of light exposure. The emission factor (emission rate at 30°C and 1000 ~molphotonm-Zs-l ) estimated by the isoprene model or extrapo- lated from measurements was similar: it was about 22 pggdw -r h-r for sun-exposed branches and 2.3 pggdw.-’ h-r for shade-adapted branches. It was rather stable over the seasons except during leaf development. The diurnal and seasonal emission patterns from Q. ibex were simulated in a satisfying way by Guenther’s algorithms especially if we excluded the laboratory variability. For shade-adapted branches, an emission factor 17 times lower had to be applied, but temperature and light responses were unchanged.
Keywords: Holm oak; index; light and temperature algorithm; Mediterranean vegetation; Modelling; Monoterpene; Quercus ilex

Effect of water stress on monoterpene emissions from young potted holm oak (Quercus ilex L.) trees - Bertin, N; Staudt, M (Oecologia, 1996)
We investigated the effects of a short period of water stress on monoterpene emissions from Quercus il- ex, a common oak species of the Mediterranean vegeta- tion and a strong emitter of monoterpenes. The experi- ment was carried out on two young saplings with a branch enclosure system under semi-controlled condi- tions. Under unstressed conditions, small qualitative (cis- [3-ocimene, trans-~3-ocimene, [3-caryophyllene and 1,8- cineol) and large quantitative (as much as 40% for the main compounds emitted) differences were observed be- tween the two apparently similar trees. Nevertheless these differences did not affect the short- and long-term responses to temperature and water stress. Daily courses of emissions and gas exchanges were similar before and after the stress. During the most severe stress, emissions were reduced by a factor of two orders of magnitude and the log-linear relationship between emissions and tem- perature no longer existed. Photosynthesis and transpira- tion rates decreased as soon as the soil started to dry, whereas monoterpene emissions slightly increased for few days and then dropped when the daily CO 2 balance approached zero. We concluded that under water stress monoterpene emissions were highly limited by monoter- pene synthesis resulting from a lack of carbon substrate and/or ATR After rewatering, both emissions and gas ex- changes recovered immediately, but to a level lower than the pre-stress level. These results have many implica- tions for monoterpene emission modelling in the Medi- terranean area, since the dry period generally extends from May to August. If our results are confirmed by field experiments, water stress could lead to a large overesti- mation of the emissions under summer conditions, when the algorithms based on light and temperature would give high emission rates.
Keywords: Holm oak; Mediterranean vegetation; monoterpene emission; Quercus ilex; water stress